القطاع الفلاحي كآلية لتفعيل التنويع الاقتصادي لتحقيق التنمية المستدامة في الجزائر - تريدي، أمينة; عجمي، سارة (جامعة الوادي University of Eloued, 2025)
تهدف الدراسة إلى إبراز دور القطاع الفلاحي في التنويع الاقتصادي لتحقيق التنمية المستدامة في الجزائر من خلال تحليل مجموعة مؤشرات إحصائية بهدف متابعة تطور مدى مساهمة القطاع الفلاحي في كل من الناتج المحلي الإجمالي والقيمة المضافة، وتوفير مناصب الشغل لقوى اليد العاملة، ومدى استغلال الأراضي الفلاحية ،وهذا بعد التطرق لأهم البرامج التنموية خلال الفترة 2010-2023، والإصلاحات الفلاحية التي استحدثتها الجزائر خلال السنوات الأخيرة. وفي الأخير خلصت الدراسة إلى أن مساهمة القطاع الفلاحي في الناتج المحلي الإجمالي تبقى نسبية وضئيلة مقارنة بالمؤهلات الطبيعية والمادية التي تمتلكها الجزائر، كما أن الجزائر تملك مساحة كبيرة لكن غير مستغلة في الفلاحة إلا بقيم قليلة جدا، إذ لا يساهم قطاع الفلاحة في زيادة مناصب التشغيل فيه. The study aims to highlight the role of the agricultural sector in economic diversification to achieve sustainable development in Algeria by analyzing a set of statistical indicators with the aim of following the development of the extent of the agricultural sector’s contribution to both the gross domestic product and value added, the provision of jobs for the labor force, and the extent of exploitation of agricultural lands. This is after, addressing the most important development programs during the period 2010-2023; and the agricultural reforms introduced by Algeria in recent years . Finally, the study concluded that the contribution of the agricultural sector to the gross domestic product remains relative and small compared to the natural and material qualifications that Algeria possesses. Algeria also has a large area, but it is not exploited in agriculture except for very small amounts, as the agricultural sector does not contribute to increasing employment positions in it.
The agricultural sector as a mechanism for activating economic diversification to achieve sustainable development in Algeria of the article, Times New Roman,
مقال
Keywords: قطاع فلاحي; تنويع اقتصادي; تنمية مستدامة; ناتج محلي إجمالي; قوى عاملة